Analysis of casualties of young car drivers in traffic accidents by gender differences: temporal trends in the Republic of Serbia - Svetlana Bačkalić; Dragan Jovanović; Smiljana Rajčević; Miloš Pljakić (International Journal of Adolescence and Youth)
Traffic accidents are a major global public health issue and the leading cause of death for individuals aged 15–29. Gender differences significantly influence traffic safety, with men and women showing distinct risk and injury patterns. This study analyzes trends in the number of casualties among young drivers (aged 18–24) in the Republic of Serbia from 1997 to 2022, disaggregated by gender. Using base and chain index, the Chow test, and joinpoint regression, the analysis reveals a declining trend in male casualties and a concerning rise in female casualties, especially after 2016. This study offers both theoretical and practical contributions. Theoretically, this research contributes to understanding gender-based risk dynamics in traffic safety. Practically, it offers critical insights for developing gender-sensitive road safety policies and interventions. Findings emphasize the need to reassess existing strategies to address the increasing exposure and vulnerability of young female drivers, supporting more effective, equitable traffic safety planning.